Serum leptin and cholesterol values in violent and non-violent suicide attempters - Atmaca, Murad; Kuloglu, Murat; Tezcan, Ertan; Ustundag, Bilal (Elsevier Ireland Ltd, 2008)
Earlier studies have linked lipid metabolism to Suicide and impulsive-aggressive behaviors. We previously reported that suicide attempters had significantly lower leptin and cholesterol levels than controls. Since lower cholesterol levels have been related to violence alone, we decided to evaluate serum total cholesterol and leptin levels in violent and non-violent Suicide attempters. In the present study, 19 violent, 16 non-violent Suicide attempters, and 20 age- and sex-matched healthy controls were compared for serum total cholesterol and leptin levels. Violent Suicide attempters had significantly lower total cholesterol and leptin levels compared with those with non-violent Suicide attempts. Our results Suggest that low serum cholesterol and leptin levels are related to the following two dimensions Of Suicide attempts: suicidality and violence. (c) 2007 Published by Elsevier Ireland Ltd.
Keywords: leptin; cholesterol; suicide; violence